Induction of labour : predicting perinatal outcome via cerebroplacental ratio among obstetric patients in Hospital Tengku Ampuan Afzan - Mohd Fairudzi Afzanizam bin Salleh (Kulliyah of Medicine, International Islamic University Malaysia, 2017)
This research sought to evaluate doppler velocimetry studies of the placenta and the fetal circulation that provide important information regarding the fetal well-being. When applied in appropriate conditions it may provide an opportunity to improve the perinatal outcome. The objectives were to assess the usefulness of cerebroplacental ratio (CPR) Doppler in predicting perinatal outcomes among women who were scheduled for induction of labor. There were 203 antenatal women recruited for CPR Doppler studies at 37week and above gestations. CPR less than 1 was taken as predictor of adverse perinatal outcomes. The adverse perinatal outcomes were evaluated by intra-partum cardiotocograph (CTG), mode of delivery, meconium-stained liquor, arterial cord blood pH, Apgar score at 5 minutes and admission to neonatal intensive care unit (NICU). Result showed that, low CPR was significantly associated with abnormal intrapartum CTG (P< 0.001), cesarean or operative deliveries for fetal compromised (P<0.001) and low arterial cord blood pH (P< 0.001). In conclusion, CPR was a valuable investigation in predicting the perinatal outcomes prior to induction of labor.